Increasing the Growth and Yield of Java Sprouts Eggplant (Solanum melongena Var. Gelatik) by Administering Different Planting Media Compositions and Rabbit Urine LOF Dosages - Rifdah Nur Safitri; Didik Utomo Pribadi; Pangesti Nugrahani (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Gelatik eggplant (Solanum melongena var. Gelatik), commonly referred to as Lalap eggplant, is a variety that can be processed into a vegetable. However, its production has declined due to the inaccurate selection of planting media compositions and the inadequate application of fertilizers. Therefore, optimizing the planting media composition and applying an appropriate dosage of rabbit urine LOF are expected to improve the growth and yield of Gelatik eggplant. The purpose of this study was (1) to examine the interaction between planting media composition and rabbit urine LOF dosage, (2) to assess the effect of planting media composition, and (3) to evaluate the effect of rabbit urine LOF dosage. The experiment was conducted in Tuban, East Java, using a Randomized Block Design (RBD) with two factors. The first factor was planting media composition, consisting of four levels: (a) soil (control), (b) soil: rice husk charcoal: manure (2:1:1), (c) soil: rice husk charcoal: manure (1:2:1), and (d) soil: rice husk charcoal: manure (1:1:2). The second factor was rabbit urine LOF dosage, also with four levels: (a) NPK (control), (b) 300 ml/plant, (c) 400 ml/plant, and (d) 500 ml/plant. The results showed that the combination of soil, rice husk charcoal, and manure (1:1:2) and 300 ml/plant of rabbit urine LOF produced a significant interaction effect on the number of fruits per plant per harvest period. Furthermore, the composition of the planting media alone (soil: rice husk charcoal: manure, 1:1:2) significantly affected plant height, leaf number, fruit weight per fruit, fruit weight per plant, and total fruit weight per plant. Similarly, rabbit urine LOF dosage alone (300 ml/plant) significantly influenced plant height, number of leaves, fruit weight per fruit, fruit weight per plant, and total fruit weight per plant.